Poets of hope and despair : the Russian symbolists in war and revolution, 1914-1918 - Hellman, Ben, 1949- (Russian history and culture, 2018)
"In Poets of Hope and Despair: The Russian Symbolists in War and Revolution (1914-1918), Ben Hellman examines the artistic responses and the philosophical and political attitudes of eight major Russian poets to the First World War and the revolutions of 1917. The historical cataclysms gave rise to apocalyptic premonitions and a thirst for a total spiritual metamorphosis. A major topic of discussion was the role of Russia in this process. Other issues raised were modern Germany, the future of a divided Poland, the occupation of Belgium, and the dilemma of the Russian Jews. In the wake of the military setbacks, hopes were mixed with feelings of fear and despair, all expressed in fictional as well as in nonfictional form"--